Web Based Learning in Pedagogical Platforms: Exploring the Integration of Web-Based Learning in Pedagogical Practices (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The new digital media are a frontier that is rich with opportunities and risks, particularly for young people. Through digital technologies, young people are participating in a range of activities, including social networking, blogging, vlogging, gaming, instant messaging, downloading music and other content, uploading and sharing their own creations, and collaborating with others in various ways. Web Based Learning (WBL) provides integrated environment of various technologies via the internet to support diverse needs of the learners. We can access information online in any number of places, such as social networks, banks, blogs, newsrooms, paid communities, etc. The paper recites on web based practices that can be embedded to the pedagogical practices by teachers, for enhancing learner. The researchers intend to focus on locating and presenting information that would be of use for pedagogical intervention in face to face to face as well as in Distance mode of education. Adequate access to a broadband internet service, basic knowledge of ICT skills and a bit of manipulating skills can help anyone become successful in their walk of life.